A high-throughput peptidomic strategy to decipher the molecular diversity of cyclic cysteine-rich peptides - Serra, Aida (2016)
Cyclotides are plant cyclic cysteine-rich peptides (CRPs). The cyclic nature is reported to be gene-determined with a precursor containing a cyclization-competent domain which contains an essential C-terminal Asn/Asp (Asx) processing signal recognized by a cyclase. Linear forms of cyclotides are rare and are likely uncyclizable because they lack this essential C-terminal Asx signal (uncyclotide). Here we show that in the cyclotide-producing plant Clitoria ternatea, both cyclic and acyclic products, collectively named cliotides, can be bioprocessed from the same cyclization-competent precursor. Using an improved peptidomic strategy coupled with the novel Asx-specific endopeptidase butelase 2 to linearize cliotides at a biosynthetic ligation site for transcriptomic analysis, we characterized 272 cliotides derived from 38 genes. Several types of post-translational modifications of the processed cyclotides were observed, including deamidation, oxidation, hydroxylation, dehydration, glycosylation, methylation, and truncation. Taken together, our results suggest that cyclotide biosynthesis involves ‘fuzzy’ processing of precursors into both cyclic and linear forms as well as post-translational modifications to achieve molecular diversity, which is a commonly found trait of natural product biosynthesis.